Investigation of Carbonyl Iron Powder for Development of Power Inductors for High Frequency. Issue 9 (6th August 2013) - Koeda, Masahito; Harada, Akihiro; Ono, Hiroyuki; Ishikura, Tomokazu; Kuroda, Tomofumi; Moro, Hideharu
SUMMARY We have investigated carbonyl iron powder (CIP) for the development of a low‐loss power inductor at about 1 MHz. Significant differences were observed for the coercivity between two kinds of CIP, nonreduction CIP and reduction CIP. In order to investigate the origin of the significant differences of coercivity, we studied two kinds of CIP. It was shown that nonreduction CIP with low coercivity is an Fe‐based nanocrystalline soft magnetic material with a high saturation magnetization. We were able to produce a low‐loss dust core using a low‐coercivity CIP at about 1 MHz. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 96(9): 46–52, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/ecj.11408